EFISIENSI SKALA DAN INTENSITAS PENGGUNAAN INPUT PADA AYAM RAS PETELUR FASE PRODUKSI KE DUA - Basir Paly (State Islamic University (UIN) Alauddin, 2015)
ABSTRACT. This study aims to determine the efficiency of a scale and intensit y of input use in laying chicken farming production phase II at Gowa. Results of this study are expected to provide additional information for further research, and for the improvement of poultry farm business management at the sites. Using survey method with data collection observation and interview. Some 30 farmers samples have been analyzed. The data collected is last 3 months include; (1) the number of population, (2) the amount of egg production per day or Henday, (3) the number of inputs used include DOC, feed, spacious cages, labor, and living cost. To determine the efficiency of a scale and intensity of input use analysts used the Cobb-Douglas production function. Results of this study concluded that the scale of production and the intensity of input use production phase II is a set of conditions that are not efficient or deccreasing return to scale (DRS). This is because the production phase II, aged 19-25 months biological production and reproductive capacity has decreased. The implications of this research is laying chicken breeders production phase II need to input a maximum of 39.80% reduction of the number of previous use.